Liberalism and other writings - Hobhouse, L. T. 1864-1929 (Cambridge University Press, 1994)
L. T. Hobhouse's Liberalism (1911), which has acquired the status of a modern classic, is the most enduring statement of the political principles which animated British liberal social reformers in the early years of the twentieth century. While written in a popular style, it is actually a theoretical work of some subtlety, combining an historical analysis of the evolution of liberal doctrine with a philosophical discussion of the character of liberal belief, and proposing a reformulation of liberalism which emphasises community, individual welfare rights, and an activist state. This 1994 edition of the work includes a number of his other writings from the same period, and will be of interest to a broad range of students and scholars in politics and the history of political thought
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte; Liberalism; State, The; Politische Theorie; Liberalismus; Sozialreform; Großbritannien; Quelle